Admiral: a 19th‐century Tyne‐built paddle tug. (1st September 2019) - Croce, Paolo; Gane, Toby
Abstract: This paper reports on the discovery in the Thames Estuary and the partial recovery and recording of the remains of a 19th‐century Tyne‐built paddle tug. The wreck is believed to be that of Admiral built in Newcastle in 1870 and sunk following a collision in the estuary in 1872. This unexpected discovery provided a rare opportunity to examine the archaeological assemblage of one these once‐familiar working vessels and revealed the continuities and innovations of a specific type of engine used on paddle tugs.